KEMAMPUAN MENULIS TEKS PROSEDUR DENGAN METODE DEMONSTRASI SISWA KELAS VII SMP N 2 KOTA SOLOK TAHUN PELAJARAN 2021/2022 - Reisty Yumeigi Monica; Redo Andi Marta; Mega Putri (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2022)
This research is motivated by the students' writing ability in learning procedure text with the demonstration method. This research is caused by the increase in students' learning motivation with active and presentative learning methods such as demonstration learning methods. This is in line with the observations and interviews that the researcher conducted with one of the Indonesian language teachers at SMP N 2 Solok City on November 25, 2021. The purpose of this study was to explain the ability to write procedural texts using the demonstration learning method of class VII students in the second semester of the academic year. 2021/2022 SMP N 2 Solok City. This research was conducted at SMP N 2 Solok City class VII. This type of research is quantitative using descriptive research methods. The research data was obtained using a performance test, which was to determine the structure and rules/language aspects of the procedure text. Data collection techniques in this study: (1) the first activity, the teacher describes the material about the procedure text, (2) the teacher provides opportunities for students to ask questions about the procedure text, (3) the teacher arranges student seats so that students can pay close attention to the text material. the procedure that the teacher will demonstrate, (4) the teacher presents a procedure text (titled making sweet tea) which is demonstrated as an exercise, (5) the teacher presents one procedure text (the title of turning off the computer (laptop) correctly) with different demonstrations for collecting data, and (6) students pay attention and write down what they see when the teacher demonstrates a procedure text. Based on the results of the study, it was found that the ability to write procedural texts with the demonstration method of students based on the structure of the procedure text was 79.35 with good qualifications and linguistic rules was 74.4 with more than adequate qualifications. Based on the results of the research described in chapter IV, it can be concluded that the ability to write procedural texts with the demonstration method of class VII students of SMP N 2 Kota Solok in the academic year 2021/2022 is 76.40 with good qualifications (B).